Aspek Pengaturan Keamanan Nasional dalam Kerangka Demokrasi - Utama, Anang Puji (Jayapangus Press, 2024)
National security serves to realise and defend the entire territory of the Republic of Indonesia. The implementation of comprehensive national security is an integral part of various aspects of the life of the nation and state, namely ideology, politics, economy, socio-culture, defence and state security. Efforts to support national development as a state goal require the regulation and management of state security. Its current arrangements continue to face challenges with concerns that its implementation violates human rights by causing a setback to democracy. This paper explores how the regulation of national security within the framework of democracy in Indonesia. The method used is narrative qualitative research with a normative legal approach. Literature study is conducted to find the meaning of the regulation of national security aspects within the framework of democracy. The source of data is through the search for relevant literature to be analysed. The findings in this paper are that Indonesia already has four important capitals that can support the regulation of national security in law while still taking into account the principles of democracy and human rights. These are the constitutional basis in the 1945 Constitution of the Republic of Indonesia, especially on human rights; the regulation of laws relating to management and institutions in national security; institutional arrangements where there is no institutional domination or every institution is equal; and the mainstreaming of the principles of human rights and democracy in government policy-making. Current conditions and future projections of the national security situation demand national security institutional arrangements by integrating Indonesia's deterrent forces to anticipate and deal with national security disturbances. Regulations in the form of laws allow the public to participate in the formulation of the material to be regulated in accordance with the formal requirements for the formation of laws, including transparency, participation and accountability.